Multilateral rules onFDI : do we need them? Will we get them? A developing country perspective - Young, Stephen (2004)
Review the state of play regarding the investment regime in the World Trade Organization, with the objective of contributing to the debate on policy priorities for developing countries. Concludes that substantial progress on an investment regime at the multilateral level is unlikely, and, without radical changes to the WTO itself and to the underlying principles of an investment regime, probably undesirable.